2021
DOI: 10.1016/j.it.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Why are there so few (or so many) circulating coronaviruses?

Abstract: Despite vast diversity in non-human hosts and conspicuous recent spillover events, only a small number of coronaviruses have been observed to persist in human populations. This puzzling mismatch suggests substantial barriers to establishment. Here, we detail hypotheses that might contribute to explain the low numbers of endemic coronaviruses, despite their considerable evolutionary and emergence potential. We assess the possible explanations ranging from issues of ascertainment, historically lower opportunitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 117 publications
0
9
0
1
Order By: Relevance
“…However, a longitudinal study showed that, while cross-reactive HCoV antibodies are boosted following SARS-CoV-2 infection, this does not correlate with protection against infection or hospitalization ( 49 ), and a lack of antibody-mediated neutralizing cross-protection has been noted between sera from SARS-CoV-1 patients and SARS-CoV-2 ( 50 ). In addition, it has been postulated that the small variety in circulating human coronaviruses may have resulted due to competition between coronaviruses filtering out potential emergent coronaviruses ( 51 ). Therefore, while there are significant amounts of corroborating evidence that some degree of cross-protection exists, the literature is not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…However, a longitudinal study showed that, while cross-reactive HCoV antibodies are boosted following SARS-CoV-2 infection, this does not correlate with protection against infection or hospitalization ( 49 ), and a lack of antibody-mediated neutralizing cross-protection has been noted between sera from SARS-CoV-1 patients and SARS-CoV-2 ( 50 ). In addition, it has been postulated that the small variety in circulating human coronaviruses may have resulted due to competition between coronaviruses filtering out potential emergent coronaviruses ( 51 ). Therefore, while there are significant amounts of corroborating evidence that some degree of cross-protection exists, the literature is not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactive antibodies are less common in pre-pandemic samples, likely due to their targeting of less conserved structural viral proteins and greater sensitivity to point mutations altering structural epitopes [ 274 , 275 ] and they have not been associated with protection from disease [ 276 ]. Nonetheless, it has been suggested that pre-existing cross-reactive immunity is the reason we have so few endemic coronaviruses, rather than lack of opportunity or lack of identification of coronavirus outbreaks in humans [ 277 ]. For another coronavirus to establish itself in the human population like SARS-CoV-2 did, it would have to circumvent significant pre-existing immunity generated by previous coronaviruses in circulation.…”
Section: How ‘Specific’ Is Sars-cov-2-specific Immunitymentioning
confidence: 99%
“…Humans, as long-lived hosts, are typically exposed multiple times in their lives to the four HCoVs and will in all likelihood be to SARS-CoV-2 in the future. Repeated exposure to the five coronaviruses in circulation is expected to restrict the immunological space that SARS-CoV-2 lineages can explore at any time [ 277 ]. The extent to which immune-escape mutations in the spike RBD act independently from each other will be critical for the emergence of new serotypes through previously unexplored epistatic combinations.…”
Section: The Good the Bad And The Uglymentioning
confidence: 99%
“…The frequency of such exposures might therefore not be the rate limiting step for outbreaks with pandemic potential. However, details of the exposure event, including viral dose, host age and immune status [ 8 , 9 ], and opportunities for onward transmission from the exposed host, may all influence the prospects of an outbreak and subsequent sustained transmission in human populations. In addition, some viruses may enter the human population lacking the capacity for efficient spread between humans, in which case adaptation to humans after a spillover event could be the critical barrier.…”
Section: Introductionmentioning
confidence: 99%